Human Rights in the Arab World - Anthony Tirado Chase, Amr Hamzawy (University of Pennsylvania Press, 2013)
Since the events of September 11, 2001 the notion of a clash between the West and the Muslim world has taken increasing hold, both explicitly in bellicose statements from many sides and implicitly in assumptions in academia and the media. Declarations of jihad1 have been met by declarations of war against absolute evil, confirming stereotypes of an essentialist clash. What has been lost in such mobilizations on the basis of ideological abstractions is precisely what extremists of various stripes hope will be lost: the articulation from within the Arab (and, more broadly, Muslim) world of a politic that directly responds to the particulars of economic, political, civil, social, and cultural rights consistently denied in the region. Human Rights in the Arab World draws attention to the status of human rights as a key barometer of the Arab world’s political health. How is human rights’ relevance defined by the Arab world’s political, social, and economic context? What are the theoretical considerations that must be taken into account regarding human rights’ implementation or, more commonly, lack thereof? This is the first English language text to collect writings of intellectuals at the forefront of debating these key issues. It is telling—and regrettable—that until now there has not been an empirical or theoretical focus on those who work within a human rights framework, or who struggle to understand the historic and contemporary place of human rights in Arab politics. The Arab world’s discourse on human rights cumulatively contradicts the assumption by many—in both the West and the Arab world—that human rights have little relevance to the region. This assumption accounts, at least in part, for the relative lack of attention paid to discourse on this subject and has limited a robust internal, regional, and transnational dialogue around human rights in the region to a very narrow audience.